Speech Assistant System With Local Client and Server Devices to Guarantee Data Privacy - Hirsch, Hans-Günter (Frontiers in Computer Science, 2022)
Users of speech assistant systems have reservations about the distributed approach of these systems. They have concerns that people might get access to the transmitted speech data or that somebody is able to access their microphone from outside. Therefore, we investigate the concept of a setup with local client and server systems. This comes along with the requirement of cost-efficient realizations of client and server. We examined a number of different cost-efficient server solutions depending on the required recognition capability of specific applications. A fairly cost-efficient solution is the use of a small computing device for recognizing a few dozens of words with a GMM-HMM based recognition. To perform a DNN-HMM based recognition, we looked at small computing devices with an integrated additional graphical processor unit (GPU). Furthermore, we investigated the use of low-cost PCs for implementing real-time versions of the Kaldi framework to allow the recognition of large vocabularies. We investigated the control of a smart home by speech as an exemplary application. For this, we designed compact client systems that can be integrated at certain places inside a room, e.g., in a standard outlet socket. Besides activating a client by a sensor that detects approaching people, the recognition of a spoken wake-up word is the usual way for activation. We developed a keyword recognition algorithm that can be implemented in the client despite its limited computing resources. The control of the whole dialogue has been integrated in our client, so that no further server is needed. In a separate study, we examined the approach of an extremely energy-efficient realization of the client system without the need of an external power supply. The approach is based on using a special microphone with an additional low-power operating mode detecting the exceeding of a preset sound level threshold only. This detection can be used to wake up the client's microcontroller and to make the microphone switch to normal operating mode. In the listening mode, the energy consumption of the microphone is so low that a client system can be active for months with an energy supply from standard batteries only.